A 28-GHz CMOS-65 nm Dual Mode Class-J Doherty Power Amplifier With Integrated Class-G Driver and Impedance-Modulated- Quadrature-Transformer Achieving 21% Back-Off Efficiency - Selvakumar Mariappan; Jagadheswaran Rajendran; Norhamizah Idros; Sofiyah Sal Hamid; Asrulnizam Bin Abd Manaf; Narendra Kumar; Abdullah Alghaihab; Arokia Nathan; Binboga Siddik Yarman (IEEE Access)
In this paper, a CMOS Class-J Doherty power amplifier (PA) integrating a Class-G driver and an Impedance-Modulated-Quadrature-Transformer (IMQT) to enhance back-off efficiency for multimode operations is presented. The Class-J Doherty PA utilizes a second harmonic termination to improve its efficiency. To further augment efficiency at deep back-off output power, a single-supply-rail Class-G driver operates with the IMQT, modulating the interstage impedance between the driver and the Doherty stages. The IMQT features a stacked transformer architecture and dynamically adjusts its impedance by switching a floating, intermediate coil between the transformer’s primary and secondary windings. A comparator regulates the IMQT based on the Class-G driver’s operation. The IMQT-DPA, fabricated using a 65nm CMOS process, operates at a center frequency of 28 GHz with a supply headroom of 1.8V. The PA achieves an average output power of 14 dBm with a back-off efficiency of 21%, representing a 1.4-fold efficiency enhancement compared to conventional Class-B operation. Under low-power mode (VDD/2) with a Class-G driver operation, the average output power is 11.3 dBm with a 1.3-fold efficiency improvement.